IMPLEMENTATION OF MULTICULTURAL EDUCATION - Ningsih, Solehati (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Multicultural education should be specifically designed so that it can help create equality and equal service for every student in these educational institutions who have cultural, racial, religious, social and economic class backgrounds. In the process of implementing multicultural education it is hoped that it will have a positive value which will later be beneficial to students. The hope in the implementation of multicultural education is firstly, it can improve self-understanding and good self-concept, secondly, in the implementation of multicultural education that is to increase the sensitivity aspect of students in understanding other people who are different from them, thirdly, to be able to feel and increase the diversity of national interpretations and also cultural aspects that are sometimes contradictory or different which also involve values and behavior, finally, with multicultural education it is hoped that this can open students' insights in dealing with differences.This study aims to find out: 1. the process of applying Multicultural Education. 2. To find out the supporting and inhibiting factors in implementing multicultural education.